Pengaruh Pembangunan Infrastruktur Terhadap Konektivitas Ekonomi Daerah di Nusa Tenggara Barat - Nur Aisyah (Economics Note, 2025)
Infrastructure development plays a vital role in strengthening regional economic connectivity, particularly in areas with limited accessibility such as Nusa Tenggara Barat (NTB). This study aims to analyze the impact of infrastructure development on economic connectivity and local growth. Using a mixed-method approach, data were collected through surveys, interviews, and secondary economic reports. Quantitative analysis was conducted using regression models, while qualitative insights were derived from stakeholder perspectives. The findings indicate that improvements in transportation networks, road quality, and port facilities significantly enhance trade efficiency, reduce logistic costs, and stimulate inter-regional investment. Moreover, infrastructure expansion has increased access to education and healthcare services, thereby improving human capital development. However, challenges remain, including uneven distribution of infrastructure benefits and environmental concerns. This research highlights the crucial role of integrated planning in ensuring inclusive economic growth. The results contribute to policy recommendations for regional governments to prioritize equitable infrastructure allocation to maximize economic connectivity and sustainability in NTB.